(untitled) (Journal of Universal Science Research, 2025)
This paper explores the concept of commentary (sharh) as a cognitive and communicative phenomenon in both literary and journalistic contexts. It highlights the historical development of commentary, its differentiation from related notions such as analysis and description, and its role in public discourse. Particular attention is given to the emergence of sports commentary in the UK and Uzbekistan, emphasizing the linguistic competence required for effective live reporting.